Prevalence and associated factors of infertility among 20–49 year old women in Henan Province, China - Liang, Shoujing; Chen, Yuanhui; Wang, Qian; Chen, Huanhuan; Cui, Chenchen; Xu, Xiaohang; Zhang, Qingwen; Zhang, Cuilian (Reproductive health, 2021)
Infertility is a reproductive health problem which affects not only individuals, families and social populations. Recently, the infertility rate in China has a trend of increase year by year, and few studies have reported the infertility rate in Henan Province, China. The aim of this study was to investigate the current prevalence and associated factors of infertility among women of childbearing age in Henan Province, China. This cross-sectional study was conducted from March 2019 to October 2019. We sampled 765 women who were 20-49 years old in eight hospitals of four cities in Henan Province, China. This survey included a questionnaire, physical examination, vaginal ultrasound examinations, and serum anti-Mullerian hormone (AMH) assessment, all of which were conducted under uniform standards by trained personnel. According to the data collected from questionnaire, participants were divided into infertile and fertile groups and analyzed associated factors. Among all the 765 participants in this study, the prevalence of infertility was 24.58%. The prevalence of primary infertility was 6.54%, and the prevalence of secondary infertility was 18.04%. In logistic multivariate regression analyses, infertility was associated with age (p < 0.001), history of gynecological surgery (p < 0.001), sweet food (p = 0.003) and decreased ovarian reserve (DOR) (p < 0.001). After further analyses, factors associated with primary infertility were age of marriage (p = 0.006), age of first sexual intercourse (p = 0.003), long-term air-conditioning environment (p < 0.001), decreased ovarian reserve (p = 0.005) and age (p = 0.002). And factors associated with secondary infertility were history of gynecological surgery (p < 0.001), decreased ovarian reserve (p = 0.002), waist-to-hip ratio (WHR) above 0.85 (p = 0.043), delivery times (p = 0.001) and ages (p < 0.001). The prevalence of infertility among women aged 20-49 was 24.58% and only 61.17% infertile women sought medical help in Henan Province, China. Age, history of gynecological surgeries and DOR may increase the risk of infertility. Local public health departments and medical professionals need to discharge their duty of reducing the high incidence of infertility and protecting women's reproductive health.